The effect of Typhoon Talim on the distribution of heavy metals on the inner shelf of the East China sea. (1st November 2021) - Lu, Jian; Li, Anchun; Dong, Jiang; Pei, Wenqiang; Feng, Xuguang; Wang, Hongli
Abstract: Surface sediment and box core samples collected from the East China Sea (ECS) inner shelf mud area before and after Typhoon Talim (2017) were analyzed for grain size, chemical elements, and heavy metals (Cr, Ni, Cu, Zn, and Pb). By comparing the results of the survey in May with those in September, we distinguished the possible sources of heavy metals, assessed heavy metal contamination status, and elucidated the impacts of summer typhoons on the distribution of heavy metals. The results of the enrichment factor (EF) and geoaccumulation index ( I geo ) showed that Cr, Ni, Zn and Pb were mainly derived from natural sources, while Cu was partly influenced by anthropogenic activities and showed minor to moderate pollution. The difference between the minimum and maximum values of heavy metals became larger after the typhoon. The distribution of heavy metals in surface sediments was positively correlated with grain sizes of 11–18 μm, while the distribution in box cores was positively correlated with grain sizes of 0.8–12 μm. Additionally, the correlation between heavy metals (except Cu in box cores) and specific grain sizes increased after the typhoon passage. The thickness of the storm layer caused by Typhoon Talim was 16 cm, and the erosion depth was 4 cm. The stations with high and low values of the enrichment factor of typhoons (EFt ) were separated from each other, indicating that heavy metal pollution increased at some stations and decreased at others after Typhoon Talim. The impact of typhoons on heavy metal pollution is related to seabed erosion and deposition. Summer typhoons can play a great role in the redistribution and burial of heavy metals, which is significant in the marine environment of the ECS. Highlights: ● Grain size and heavy metals were analyzed before and after Typhoon Talim. ● Copper was partly influenced by anthropogenic activities. ● The thickness of the storm layer caused by Typhoon Talim was 16 cm. ● The typhoon impact on heavy metals was related to seabed erosion and deposition.